In Degraded Lands... Brahmi cultivation fetches more - Saran, P L; Devi, Ganga; Kumar, Jiendra (Indian Horticulture, 2019)
Brahmi cultivation plays an important role in low-laying area, especially in central Gujarat for livelihood. Integration of brahmi into existing farming systems was thought to be one of the viable options for poor farmers. Even brahmi could bring high return per rupee investment and better productivity. The agri-economics of brahmi have also been worked out to attract its adoption by farmers. On an average, a farmer can get an approximately `2,49,000/- ha/year as net return with a benefit:cost ratio of 2.99. Brahmi growers not only get the remunerative income, but it also provides employment opportunities to the local people. Thus, its cultivation is a profitable venture under low-lying area of central Gujarat.